Penerapan Sistem Publikasi Informasi Humas dalam Meningkatkan Validitas Informasi di Website Kementerian Agama Provinsi Sumatera Selatan - Riska Amelia; Kusnadi Kusnadi; Manalullaili Manalullaili (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2018)
This research was carried out on public relations in the Ministry of Religion of South Sumatra Provincewhich has implemented an information publication system to improve the validity of information on the website of the Ministry of Religion of South Sumatra Province.The background of this research isbased on Law No. 14 of 2008concerning Public Information Openness and ISO / IEC 20071 of 2009 concerning Information Security Management System Requirements. The work unit in the Ministry of Religion of South Sumatra implements a standard for the control of online media, namely the information publication system.Thisinformation publication system with the purpose of controlling information published on the website.This research uses qualitative data, where the primary data sources are public relations staff, SOP information system and website of the Ministry of Religion of South Sumatra Province.The theorythis research is the Grunig and Hunt Situation Theory of public information needs and Shannon and Weaver's information theory.The results of this research are the application of this information publication system with 5 control books can improve the validity of information because the published information can be more clearly and accurately.